Resistance to Mycobacterium leprae in Mice Infected with Toxoplasma gondii and Besnoitia jellisoni - Krahenbuhl, James L. (1974)
Mice chronically infected with the intracellular protozoan Toxoplasma gondii or Besnoitia jellisoni were resistant to footpad challenge with Mycobacterium leprae. Resistance was manifested by lower numbers of recoverable M. leprae in the footpads of protozoal-infected mice and was enhanced in Toxoplasma-infected mice by a booster injection of Toxoplasma antigen in the infected footpad. The results suggest a major role for the activated macrophage in the control of M. leprae infection.